Una generazione che cambia Civismo, solidarietà e nuove incertezze dei giovani della provincia di Firenze - BAGLIONI, LORENZO GRIFONE (Strumenti per la didattica e la ricerca, 2007)
Despite the evident importance of the youth question in the ambit of modern society, in practice the consideration of young people as a category of consumers frequently prevails over the valorisation of their role as citizens. This survey - triggered by a synergy between the Provincial Authority and the University - focuses the attitudes and orientations of young people, both Italian and immigrants, in the Province of Florence. The objective is to bring to the fore the dynamic and more strictly civic aspect, so as to explore themes such as the shifts in values and the security, identity and participation of the new generations. The analysis effectively brings to light a widespread ambivalence, comprising both the innovative characteristics of individualism and other features that hark back to traditionally consolidated legacies. What emerges is the sense of a social mutation that is already under way, but still in transition, in which young people play a role of considerable significance.